Wearable Monitors Facilitate Exercise in Adult and Pediatric Stem Cell Transplant. Issue 3 (July 2021) - Pottebaum, Ethan; Warmoth, Alexa; Ayyappan, Sabarish; Dickens, David S.; Jethava, Yogesh; Modi, Arunkumar; Tomasson, Michael H.; Carr, Lucas J.; Bates, Melissa L.
Abstract : Hematopoietic stem cell transplant (HSCT) is a potentially curative treatment for hematopoietic malignancies, complicated by decreased performance status and quality of life. Exercise therapy improves outcomes in HSCT, but several barriers have prevented exercise from becoming routine clinical practice. Based on existing data that wearable technologies facilitate exercise participation in other sedentary and chronic illness populations, we propose the novel hypothesis that wearable technologies are a valuable tool in transcending barriers and developing exercise therapy programs for HSCT patients. Abstract : Wearable technology can be valuable additions to exercise interventions for hematopoietic stem cell transplant patients.